Tren Hijrah dan Dai Prematur: Analisis Fenomena Sosial dan Implikasinya dalam Dakwah Kontemporer - Harifah, Nurul (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The phenomenon of hijrah is increasingly popular among Indonesian urban communities, especially among the younger generation. However, this trend has also given rise to the phenomenon of